The role of pharmacy in advancing evidence-based tobacco use treatment in the Veterans Health Administration - Timothy C Chen; Mark C Geraci; Mark G Myers; Dana E Christofferson; Jennifer Knoeppel; Michael H Tran; Kim W Hamlett-Berry; Pamela S Belperio (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose Pharmacy has been a key driver of enhanced patient access to tobacco use treatment in the Veterans Health Administration (VHA). The purpose of this article is to describe steps taken by VHA, particularly in integrating pharmacy expertise, to improve tobacco use treatment among veterans and their impact on pharmacotherapy prescribing. Summary Over the past 15 years, VHA policy has expanded patient access to tobacco use treatment medications and developed clinical practice models and training programs that integrate clinical pharmacist practitioners (CPPs) in the delivery of evidence-based tobacco use treatment. As a result of these policies and programs, prescribing of tobacco use treatment medications by CPPs increased almost 3-fold from 2014 to 2023 and over 50% of CPPs prescribe tobacco use treatment medications. CPPs accounted for approximately 30% of varenicline, nicotine nasal spray, and nicotine inhaler prescriptions in VHA in 2020, despite making up only 14% of all prescribers in VHA. Conclusion With significant support from pharmacy providers, VHA has made great strides in increasing access to evidence-based care. The lessons learned from VHA may support other healthcare systems in increasing tobacco use treatment through use of pharmacy-led clinical programs.